2021
DOI: 10.1002/hbm.25592
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus‐related decreases in corpus callosal integrity and corresponding increases in functional connectivity

Abstract: People living with human immunodeficiency virus (PLWH) often have neurocognitive impairment. However, findings on HIV-related differences in brain network function underlying these impairments are inconsistent. One principle frequently absent from these reports is that brain function is largely emergent from brain structure. PLWH commonly have degraded white matter; we hypothesized that functional communities connected by degraded white matter tracts would show abnormal functional connectivity. We measured whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 130 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…Existing research has also suggested a correlation between corpus callosum abnormalities and an increased predisposition to epilepsy and other neurological disorders [ 17 19 ]. The corpus callosum is well-recognized for its fundamental role in facilitating communication between both brain hemispheres, and any aberrations in its development can result in cognitive and developmental challenges [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing research has also suggested a correlation between corpus callosum abnormalities and an increased predisposition to epilepsy and other neurological disorders [ 17 19 ]. The corpus callosum is well-recognized for its fundamental role in facilitating communication between both brain hemispheres, and any aberrations in its development can result in cognitive and developmental challenges [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[59] The lack of aggressive HIV associated WM damage in the CC after cART suggested that early treatment is neuroprotective to the CC to some extent. [74] On one hand, cART may contribute to synaptic injury via oxidative stress as has been demonstrated in vitro and in animal models[75]. On the other hand, early and continuous antiretroviral therapy can be neuroprotective, limiting the damage to white matter.…”
Section: Discussionmentioning
confidence: 99%
“…This CTG algorithm summarizes connectivity in canonical, well-characterized fiber systems. Streamline connectivity between regions of interest (ROIs) of a sub-parcellated version of the Harvard-Oxford Atlas ( Tzourio-Mazoyer et al, 2002 ), defined originally in MNI space, and used previously in our work ( Beynel et al, 2020 , Davis et al, 2017 ) and others ( Hall et al 2021 ). One disadvantage of this standard atlas is that the ROIs could have different sizes.…”
Section: Methodsmentioning
confidence: 99%